EUROPEAN SOCIETY AND HUMAN CAPITAL: ASSESSMENT OF EU LEGISLATION ON SOCIAL COHESION AND HUMAN VALUES - Anca Parmena Olimid (Economics & Education, 2023)
Objectives. The aim of this paper is to reflect on the legislation of the European Union (hereinafter EU) regarding human capital, human values and social cohesion by presenting two main approaches: (1) the relevant legislation underlining the protection of human capital, human values and social cohesion in the European society; (2) the social mechanisms and related concepts of governance, social entrepreneurship and active citizenship of the EU, focusing on providing different approaches to the economic, historical and legal phenomena and processes. Methodology. The research uses the qualitative methods of thematic analysis and legal documentation and it focuses on (1) the legal collection provided by the EUR-Lex database depending on the selected period (2006-2023) and the domain of the document by using the legal and network analysis of EU documents using the selection criteria of document number and document type; (2) the exploration of the systematic bibliography involving documentation and research on the links between human capital, human values and social cohesion. Results and discussion. The results of the research highlight the role of EU legislation and scientific knowledge in a multidisciplinary and multifaceted analysis. Conclusions: In conclusion, the subject of the study is an open debate, involving both the theoretical understanding and the mechanisms of EU multi-level governance.